Pembelajaran Kewirausahaan dalam Minat Berwirausaha Siswa Kelas XII SMKN 1 Jerowaru Jurusan Tata Boga - Sukranudin, Sukranudin (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
The purpose of this study was to investigate the impact of entrepreneurship education on the entrepreneurial talent of grade XII culinary arts students at SMKN 1 Jerowaru. Employing a quantitative research methodology characterized by associative causality, the research population consisted of all grade XII students in the culinary arts program. A probability sampling technique was utilized to select participants, and data were collected through structured questionnaires. Statistical regression analysis was performed using SPSS for Windows version 17 to assess the relationships among variables. The analysis revealed that the data followed a normal distribution, with a significance level of less than 0.05. The regression model established was Y = 1.105 X1 + 0.589, yielding a t-value of 6.579 and an R² value of approximately 0.653. These findings indicate that entrepreneurship education explains 65% of the variance in students' interest in entrepreneurship, suggesting that external factors account for the remaining 35%. The results underscore the significant influence of entrepreneurship education on enhancing business acumen among culinary arts students, indicating a high level of interest in entrepreneurial ventures. This study contributes to the existing literature by highlighting the critical role of educational interventions in fostering entrepreneurial skills, thereby offering implications for curriculum development aimed at reducing unemployment through enhanced entrepreneurial engagement.